2019
DOI: 10.1007/s40195-019-00949-5
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Evolution and Mechanical Behavior of Friction-Stir-Welded DP1180 Advanced Ultrahigh Strength Steel

Abstract: Friction stir lap welding of a DP1180 advanced ultrahigh strength steel was successfully carried out by using three welding tools with different pin lengths. The effects of the welding heat input and material flow on the microstructure evolution of the joints were analyzed in detail. The relationship between pin length and mechanical properties of lap joints was studied. The results showed that the peak temperatures of all joints exceeded A c3 , and martensite phases with similar morphologies were formed in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…Furthermore, according to the corresponding energy spectrum shown in figure 4(g), it can be found that Cr element existed in this carbide marked by red circle in figure 4(e). And from the selected area electron diffraction (SAED) pattern along the [562] zone axis of the carbide illustrated in figure 4(h), this carbide has an orthogonal structure which is just consistent with that of θ-Fe 3 C. Therefore, this carbide is confirmed to be θ-(Fe, Cr) 3 C. In fact, carbon atoms or other alloy elements still have a certain diffusion ability to segregate on dislocations or other crystal defects, and carbides can precipitate dispersedly after quenching, which is called the self-tempering phenomenon of martensite [21]. And the deformation strengthening effect of reducing is also helpful to diffusion and precipitation of carbides by supplying more precipitation sites.…”
Section: Microstructure Characteristics Of Tmcpsupporting
confidence: 60%
“…Furthermore, according to the corresponding energy spectrum shown in figure 4(g), it can be found that Cr element existed in this carbide marked by red circle in figure 4(e). And from the selected area electron diffraction (SAED) pattern along the [562] zone axis of the carbide illustrated in figure 4(h), this carbide has an orthogonal structure which is just consistent with that of θ-Fe 3 C. Therefore, this carbide is confirmed to be θ-(Fe, Cr) 3 C. In fact, carbon atoms or other alloy elements still have a certain diffusion ability to segregate on dislocations or other crystal defects, and carbides can precipitate dispersedly after quenching, which is called the self-tempering phenomenon of martensite [21]. And the deformation strengthening effect of reducing is also helpful to diffusion and precipitation of carbides by supplying more precipitation sites.…”
Section: Microstructure Characteristics Of Tmcpsupporting
confidence: 60%
“…Owing to the reversion and recrystallisation of deformed grains and tempering of martensite, fine ferrite was generated and carbide particles could be easily precipitated in this region (Figure 4(h)). Specified explanation of the microstructural evolution in the sub-HAZs could be found in our previous work [29].…”
Section: Resultsmentioning
confidence: 99%
“…It was noticed that there was no visible thermomechanical affected zone (TMAZ) in the welds. The allotropic phase transitions that occurred during carbon steel friction stir welding remove the evidence of (TMAZ) [19]. The HAZ in the FSLW joint is divided into three zones, namely the crucial heat-affected zone (CHAZ), nuclear heat-affected zone (NHAZ), and peripheral heat-affected zone (PHAZ), as quoted by Mahdi Mahmoudiniya et al [4].…”
Section: Macrolevel Zones In Fslw and Fsslw Jointsmentioning
confidence: 94%
“…Z.W. Wang et al [19] also discussed the tool movement's influences on the joint's strength and fracture mode. As the TTS increases, because of the lower heat, the effective lap width reduces, reducing the joint's strength.…”
Section: The Effect Of Welding Variables and Determining Optimal Cond...mentioning
confidence: 99%
See 1 more Smart Citation